Frequency dependent stiffness and damping coefficients of orifice compensated multi-recess hydrostatic journal bearings - Ghosh M.K.; Viswanath N.S. (My University, 2025)
Frequency dependent stiffness and damping characteristics of an orifice compensated multi-recess hydrostatic journal bearing has been presented incorporating recess volume fluid compressibility effects into it. The theory is based on linearising the Reynolds' equation for finite bearings and the recess flow continuity equation using first order perturbations. A new dimensionless recess volume fluid compressibility parameter (γ) has been introduced. Results for stiffness and damping characteristics have been presented for various frequency of vibration or squeeze parameters (σ) and recess volume parameters (γ) in addition to the usual bearing design parameters. © 1987.